The Reckless Driving Behaviors Among Vehicle Drivers in Qatar - Thani, Faisal bin Abdulaziz Al (Journal of Cultural Analysis and Social Change, 2025)
This study examines reckless driving behaviors among drivers in Qatar, focusing on demographic, psychological, and social influences. Predominantly male participants (94.3%) aged 25-40 years (79.5%) and mostly educated (64.8% bachelor’s degree) reported their behaviors. Key findings identified impulsiveness and peer influence as major causes, emphasizing the need for targeted interventions and policy measures. The research, based on a social survey of 88 drivers, highlighted physical activity, desire for social approval, provocation, risk-taking, and impulsivity as primary factors. Recommendations include engaging governmental and civil organizations to address these issues and suggesting further research on psychological, social, and cultural aspects of reckless driving.